Comparison of the learning outcomes between flipped classroom and interactive lectures among medical undergraduates - Simi Kurian; Manu Mathews; Binoo Divakaran (Asian Journal of Medical Sciences)
Background: Flipped classroom is a novel teaching-learning method which is more learner-centered. Here there is active involvement by students and more teacher-student interaction.